2011
DOI: 10.1073/pnas.1018985108
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic reconfiguration of human brain networks during learning

Abstract: Human learning is a complex phenomenon requiring flexibility to adapt existing brain function and precision in selecting new neurophysiological activities to drive desired behavior. These two attributes-flexibility and selection-must operate over multiple temporal scales as performance of a skill changes from being slow and challenging to being fast and automatic. Such selective adaptability is naturally provided by modular structure, which plays a critical role in evolution, development, and optimal network f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

78
1,809
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,532 publications
(1,895 citation statements)
references
References 56 publications
78
1,809
2
6
Order By: Relevance
“…These networks of regions with coherent activity during rest are consistent across subjects and closely resemble the brain's functional organization of evoked responses (Damoiseaux et al, 2006;Fox and Raichle, 2007;Laird et al, 2011;Smith et al, 2009). Coherent BOLD activity persists during sleep and in anesthetized monkeys, suggesting that it reflects a fundamental property of the brain's functional organization (Larson-Prior et al, 2009;Vincent et al, 2007).Coherent BOLD activity, known as "functional connectivity" (FC), is modulated by learning (Bassett et al, 2011), cognitive and affective states (Cribben et al, 2012;Ekman et al, 2012;Eryilmaz et al, 2011;Richiardi et al, 2011;Shirer et al, 2012) and also spontaneously Chang and Glover, 2010; Kitzbichler et al, 2009). Chang andGlover (2010) showed that FC between the posterior cingulate cortex, a key region of the default mode network, and various other brain regions was highly dynamic over time.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…These networks of regions with coherent activity during rest are consistent across subjects and closely resemble the brain's functional organization of evoked responses (Damoiseaux et al, 2006;Fox and Raichle, 2007;Laird et al, 2011;Smith et al, 2009). Coherent BOLD activity persists during sleep and in anesthetized monkeys, suggesting that it reflects a fundamental property of the brain's functional organization (Larson-Prior et al, 2009;Vincent et al, 2007).Coherent BOLD activity, known as "functional connectivity" (FC), is modulated by learning (Bassett et al, 2011), cognitive and affective states (Cribben et al, 2012;Ekman et al, 2012;Eryilmaz et al, 2011;Richiardi et al, 2011;Shirer et al, 2012) and also spontaneously Chang and Glover, 2010; Kitzbichler et al, 2009). Chang andGlover (2010) showed that FC between the posterior cingulate cortex, a key region of the default mode network, and various other brain regions was highly dynamic over time.…”
mentioning
confidence: 58%
“…Previous studies reported large-scale reorganizations of whole-brain functional brain networks during learning (Bassett et al, 2011), task preparation (Ekman et al, 2012), or rest (Allen et al, in press). Bassett et al (2011) studied dynamic community organization, Ekman et al (2012) predicted upcoming tasks and errors from network measures (e.g.…”
Section: Related Methodsological Studiesmentioning
confidence: 99%
See 3 more Smart Citations